Factors Affecting Purchasing Decisions on Wardah Cosmetics : (Case Study: People in Medan City) - Edji, Syahdani Nazwa; Yenni Samri Juliati Nasution; Khairina Tambunan (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine and analyze the factors that influence purchasing decisions on wardah cosmetics among the people of Medan city. This research uses a quantitative approach. The data used in this study are primary data obtained from questionnaires. The sample of this study was the people of the city of Medan, totaling 100 respondents. The analysis technique uses multiple linear regression analysis. The results of the study partially show that influencing factors such as taste, income, price, lifestyle, and halal labeling have a positive and significant effect on purchasing decisions. The results of the study simultaneously show that influencing factors such as taste, income, price, lifestyle, and halal labeling have a positive and significant effect on purchasing decisions.